Intensity determination of the scattering rates in the monolayer graphene - V. V. Murav'ev; V. N. Mishchenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of simulation of the electron scattering rates in a single graphene layer without substrate are presented. High mobility of charge carriers, maximally obtained among all known materials, makes graphene a promising material for the creation of new semiconductor devices with good output characteristics. The prevalence of electron-electron scattering over other types of scattering in the region of moderate field energy in a single graphene layer is established. The investigated dependences of the rates of carrier scattering will enable to obtain the main characteristics of charge carrier transfer in semiconductor structures containing graphene layers by modeling using the Monte Carlo method.